Cash transfers and child nutritional outcomes: a systematic review and meta-analysis - James Manley; Yarlini Balarajan; Shahira Malm; Luke Harman; Jessica Owens; Sheila Murthy; David Stewart; Natalia Elena Winder-Rossi; Atif Khurshid (BMJ Global Health)
Background Cash transfer (CT) programmes are implemented widely to alleviate poverty and provide safety nets to vulnerable households with children. However, evidence on the effects of CTs on child health and nutrition outcomes has been mixed. We systematically reviewed evidence of the impact of CTs on child nutritional status and selected proximate determinants.Methods We searched articles published between January 1997 and September 2018 using Agris, Econlit, Eldis, IBSS, IDEAS, IFPRI, Google Scholar, PubMed and World Bank databases. We included studies using quantitative impact evaluation methods of CTs with sample sizes over 300, targeted to households with children under 5 years old conducted in countries with gross domestic product per capita below US$10 000 at baseline. We conducted meta-analysis using random-effects models to assess the impact of CT programmes on selected child nutrition outcomes and meta-regression analysis to examine the association of programme characteristics with effect sizes.Results Out of 2862 articles identified, 74 articles were eligible for inclusion. We find that CTs have significant effects of 0.03±0.03 on height-for-age z-scores (p<0.03) and a decrease of 2.1% in stunting (95% CI −3.5% to −0.7%); consumption of animal-source foods (4.5%, 95% CI 2.9% to 6.0%); dietary diversity (0.73, 95% CI 0.28 to 1.19) and diarrhoea incidence (−2.7%, 95% CI −5.4% to −0.0%; p<0.05). The effects of CTs on weight-for-age z-scores and wasting were not significant (0.02, 95% CI −0.03 to 0.08; p<0.42) and (1.2%, 95% CI: −0.1% to 2.5%; p<0.07), respectively. We found that specific programme characteristics differentially modified the effect on the nutrition outcomes studied.Conclusion We found that CT programmes targeted to households with young children improved linear growth and contributed to reduced stunting. We found that the likely pathways were through increased dietary diversity, including through the increased consumption of animal-source foods and reduced incidence of diarrhoea. With heightened interest in nutrition-responsive social protection programmes to improve child nutrition, we make recommendations to inform the design and implementation of future programmes.